Pengaruh Komunikasi terhadap Kinerja Karyawan Fior Lotus : (Studi pada Suatu UMKM di Ciomas, Kabupaten Bogor) - Auf Farras Naufal; Suhroji Adha (Global Leadership Organizational Research in Management, 2024)
In this life we ​​cannot be separated from communication. In a company, every employee needs to communicate. Communication can influence employee performance. Good communication can make an employee's performance good and conversely bad communication can make an employee's performance bad. The purpose of writing this scientific work is to determine the relationship between communication and the performance of Fior Lotus employees and to determine the influence of communication on the performance of Fior Lotus employees. Fior Lotus itself is a Small and Medium Enterprise (SME) in the Ciomas area, Bogor Regency. Fior Lotus uses Shopee to sell its products. They have around 76,100 followers on Shopee. In an average day they sell 300 - 400 pairs of shoes The research used used qualitative methods. Meanwhile data collection was carried out using the interview method. From the data obtained after conducting interviews, the author found that communication is positively related or has a relationship with the performance of Fior Lotus employees and communication has a great influence on their performance which is characterized by their increasing productivity.